Optimizing Industrial Processes through Digital Twin Simulation in a Didactic Manufacturing Plant - Guimarães, João F. R.; Gaudio, Mateus; Carvalho, Gabriel; Andreão, Rodrigo; Ribeiro, Saulo; Ferreira, Ramon; Ribeiro, Maria; Zago, Gabriel (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
This paper showcases a project employing a didactic manufacturing plant to embody the concept of a Digital Twin and optimize industrial processes. The plant, which simulates an industrial process, includes components like pistons, conveyor belts, and a robotic arm. The Digital Twin is crafted using Unity 3D, a robust platform for developing virtual reality applications. The project concentrates on two operational modes: Digital Shadow Mode, emulating real-time operation through external sensors, and Simulation Mode, facilitating the enhancement and optimization of production parameters. An iterative algorithm is devised to automatically tweak operational parameters, boosting efficiency. The results affirm the efficacy of the Digital Twin approach in optimizing industrial processes.